2018
DOI: 10.1016/j.phrs.2017.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Functional histamine H 3 and adenosine A 2A receptor heteromers in recombinant cells and rat striatum

Abstract: In the striatum, histamine H receptors (HRs) are co-expressed with adenosine A receptors (ARs) in the cortico-striatal glutamatergic afferents and the GABAergic medium-sized spiny neurons that originate the indirect pathway of the basal ganglia. This location allows HRs and ARs to regulate the striatal GABAergic and glutamatergic transmission. However, whether these receptors can physically interact has not yet been assessed. To test this hypothesis, a heteromer-selective in vitro assay was used to detect func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The density of dopamine D 2 receptors in striatal nerve terminals was evaluated in a synaptosomal membrane preparation obtained as described in detail elsewhere (Márquez-Gómez et al, 2018) from a pool of P21 males or females (four pups per determination for a total of three experiments per group). Synaptosomes were lysed in a hypotonic solution (10 mM Tris–HCI, 1 mM EGTA, pH 7.4), the suspension was centrifuged (20,000 × g , 4°C, 20 min) and the pellet (membranes) was re-suspended in 0.5 ml incubation buffer (50 mM Tris–HCI, 10 mM KCl, 4 mM MgCl 2 , 1 mM EDTA, 100 μM ketanserin, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…The density of dopamine D 2 receptors in striatal nerve terminals was evaluated in a synaptosomal membrane preparation obtained as described in detail elsewhere (Márquez-Gómez et al, 2018) from a pool of P21 males or females (four pups per determination for a total of three experiments per group). Synaptosomes were lysed in a hypotonic solution (10 mM Tris–HCI, 1 mM EGTA, pH 7.4), the suspension was centrifuged (20,000 × g , 4°C, 20 min) and the pellet (membranes) was re-suspended in 0.5 ml incubation buffer (50 mM Tris–HCI, 10 mM KCl, 4 mM MgCl 2 , 1 mM EDTA, 100 μM ketanserin, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…At presynaptic terminals, H3R not only acts as a heteroreceptor, which suppresses transmitter release [ 36 ] and modulates striatal medium spiny neuron (MSN) activity [ 37 ], but also forms with adenosine A 2a receptor (A 2a R) as the heteromers [ 38 ]. Activation of H3R increases the A 2a R activity-induced cAMP formation [ 38 ], and causes neurotransmitter release [ 39 ]. Adenosine A 2a R has been shown to increase glutamatergic release from corticostriatal terminals [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coronal slices (300 μm thick) were then obtained with a vibratome (World Precision Instruments, Sarasota, FL), and the pallidal tissue was carefully dissected from the slices [16]. The composition of the Krebs-Henseleit solution was (mM) NaCl 116, KCl 3, MgSO 4 1, KH 2 PO 4 1.2, NaHCO 3 25, and D-glucose 11 (pH 7.4 after saturation with O 2 /CO 2 , 95:5% v/v). This solution did not contain CaCl 2 in order to reduce excitotoxicity.…”
Section: Preparation Of Slices and Synaptosomesmentioning
confidence: 99%
“…In transfected cells, H 3 Rs form heteromers with dopamine D 1 and D 2 receptors, and in striatal membranes, H 3 R activation decreases the affinity of D 2 receptors for agonists [23], whereas in SK-N-MC cells shifts the coupling of D 1 receptors from Gα s to Gα i/o proteins and therefore from stimulation to inhibition of cAMP formation [24]. We recently showed that endogenous and transfected H 3 and A 2A receptors form heterodimers [25], which could therefore underlie the interaction H 3 R/A 2A R in GABA release.…”
Section: Effect Of H 3 R Activation On the Affinity Of A 2a Rs For The Agonist Cgs-21680mentioning
confidence: 99%